Phylotype classification of Ralstonia solanacearum biovar 1 strains isolated from banana (Musa spp) in Malaysia - Mohamed Zulperi, Dzarifah; Sijam, Kamaruzaman; Mior Ahmad, Zainal Abidin; Awang, Yahya; Mohd Hata, Erneeza (Taylor & Francis, 2014)
During 2011–2012, 15 bacterial isolates were obtained from wilting banana plants from seven locations in Malaysia. Characterisation of the Malaysian isolates was determined by biovar determination, pathogenicity test, phylotype-specific multiplex PCR (Pmx-PCR) and endoglucanase (egl) gene amplification. Based on the genotype, phenotype and pathogenic characteristics, all isolates were identified as Ralstonia solanacearum. Pmx- and egl-PCRs indicated that all isolates belong to phylotype II of Ralstonia species complex hierarchical classification. The neighbour joining phylogenetic tree of egl sequences also verified the results where the isolates were all clustered into phylotype II, together with the reference sequences strains, UW070 and UW162. Therefore, the results of our study may provide a better understanding on the taxonomy of R. solanacearum species occupying banana plantations in Malaysia. This study is indeed the first report of phylotype II classification of R. solanacearum biovar 1 strains isolated from banana plants in Malaysia.